IPod & iTunes : the missing manual - Biersdorfer, J. D. (Missing manual., 2004)
The iPod is the world's bestselling music player. But if you think that it's just a music player, then you must think Clark Kent is just a newspaperman. In this freshly updated edition, New York Times tech columnist J. D. Biersdorfer blows open the secret doors of this gleaming, chrome-and-white beauty. With humor and authority, she lays bare an astonishing collection of useful tips, tricks, and shortcuts like these: iPod as PalmPilot . The iPod can suck in your calendar, address book, to-do list, and notes from a Mac or PC, and then display them at the touch of a button. It also doubles as an alarm clock and stopwatch. iPod as hard drive . You can use your iPod to carry gigantic files from place to place. iPod as e-book . The iPod makes an excellent book reader, capable of scrolling through recipes, driving directions, and even Web pages. iPod as GameBoy . The iPod's games are perfect time-killers for waiting rooms, bus rides, and the Department of Motor Vehicles. iPod and iTunes: The Missing Manual , 2nd Edition is much more than it seems, too. It not only covers all iPod models for both Mac and Windows, including the iPod Mini, it's also the ultimate guide to the iTunes software, MusicMatch Jukebox, and the new iTunes Music Store for both Mac and Windows. No matter what kind of music moves you, iPod and iTunes: The Missing Manual , 2nd Edition will help you get much more out of your iPod--and much more into it.